Disparities in Hispanic/Latino and non-Hispanic Black men with low-risk prostate cancer and eligible for active surveillance: a population-based study. Issue 4 (November 2018) - Katz, Jonathan; Chinea, Felix; Patel, Vivek; Balise, Raymond; Venkatramani, Vivek; Gonzalgo, Mark; Ritch, Chad; Pollack, Alan; Parekh, Dipen; Punnen, Sanoj
Abstract Background Non-Hispanic Black (NHB) men are at an increased risk for aggressive prostate cancer (PCa), making active surveillance (AS) potentially less optimal in this population. This concern has not been explored in other minority populations—specifically, Hispanic/Latino men. We recently found that Mexican-American men demonstrate an increased risk of PCa-specific mortality, and we hypothesized that they may also be at risk for an adverse outcome on AS. Methods Using the Surveillance, Epidemiology, and End Results (SEER) program, we extracted a population-based cohort of men diagnosed from 2004 to 2013 with localized or regional PCa, who had ≤2 cores of only Grade Group (GG) 1 cancer, and underwent radical prostatectomy (RP) with available biopsy and surgical pathology results. We measured discovery of high-risk PCa at RP and collected socioeconomic status (SES) data across different racial/ethnic groups. We defined aggressive tumors as either an upgrade to GG 3 or higher (GG3+) cancer or non-organ-confined disease (≥pT3a or N1). Univariate and multivariate logistic regression models were developed to assess the association between racial/ethnic categories and the previously mentioned adverse oncologic outcomes both with and without adjusting for SES factors. Results NHB and Mexican-American men were significantly more likely to have aggressive PCa, following RP. In multivariable logistic regression adjusting for SES factors and relative to non-Hispanic White (NHW) men, Mexican-American men had at increased odds of upgrading to GG3+ (OR 1.67; 95% CI [1.00–2.90]). NHB men were more likely to have non-organ-confined disease (OR 1.34; 95% CI [1.06–1.69]), while Mexican-American men had a similar risk to NHW men. Conclusion Among individuals with low-risk PCa and eligible for AS, Mexican-American and NHB men are at an increased risk of harboring more aggressive disease at RP. This novel finding among Mexican-Americans deserves further evaluation.